(untitled) (BIRDEM Medical Journal, 2014)
Most clinicians consider a peripheral nerve lesion in patients with drop foot. However, causes stemming from the central nervous system represent rare, important, and underappreciated differential etiologies. Central causative lesions usually occur at locations where pyramidal tract connections are condensed and specific and the function is somatotopically organized. Here we report case presenting as central foot drop or spastic foot-drop and other myriad clinical features which after investigations was found due to bilateral parasagittal meningiomas. DOI: http://dx.doi.org/10.3329/birdem.v4i1.18559 Birdem Med J 2014; 4(1): 52-55